E-014 In vitro neurovascular model and particulate characterization of liquid embolics. (22nd July 2018) - Cotter, T; LoGrande, K; Almutairi, M; Aldhufairi, S; Settanni, C; Gonzalez, C; Ducruet, A; Becker, T
Abstract : Introduction/purpose: To refine the development of novel endovascular devices and materials, innovative experimental testing methods can assess blood flow effects, material fatigue, downstream migration, and particulation. Specifically, in vivo animal models are not ideal for assessment of downstream particulation. This study describes the development of an in vitro neurovascular model to quantify particulation risks from endovascular devices. Materials and methods: A flow loop simulates neurovascular blood flow and pressures. The model is controlled by a pump and a temperature-controlled (TC) fluid reservoir (to maintain 37°C). A LabVIEW monitoring system records and displays real-time data from pressure transducers, flow meters, and thermocouples connected to the flow loop. The pump delivers 250 ml/min (tunable to physiological conditions) and generates a mean pressure of 100 mmHg to the attached vessel phantoms. Distal to the phantoms are in-line filters to capture particles above 5.0 µm (figure 1). After a simulated endovascular procedure, filters are removed for analysis. The model can characterize the short- and long-term performance of devices delivered to vessel defects, such as aneurysms. Results: The device tested was a liquid embolic (PPODA-QT). Microcatheters were placed into the aneurysm phantom using endovascular surgical techniques. Fluoroscopic imaging monitored the PPODA-QT delivery. Particle assessment was conducted by filter analysis (optical and electron microscopy) and liquid sample analysis (in-line interference holography) of downstream particle size and quantity and compared to the release specification for injectable fluids (USP <788 >– table 1). Conclusions: Development of novel devices for neurovascular treatments requires robust modeling to ensure both short-and long-term effectiveness without downstream migration. This venture is a synergistic collaboration between the bioengineering and neurointerventional fields, and this study is ultimately important for providing physicians with a better understanding of non-thrombus downstream effects from neurovascular devices and materials. Disclosures: T. Cotter: 1; C; National Institutes of Health. 4; C; Aneuvas Technologies, Inc. 5; C; Aneuvas Technologies, Inc, Barrow Neurological Institute, Northern Arizona University. K. LoGrande: None. M. Almutairi: None. S. Aldhufairi: None. C. Settanni: None. C. Gonzalez: 1; C; National Institutes of Health. 4; C; Aneuvas Technologies, Inc. 5; C; Aneuvas Technologies, Inc, Barrow Neurological Institute. A. Ducruet: 1; C; National Institutes of Health. 4; C; Aneuvas Technologies, Inc. 5; C; Aneuvas Technologies, Inc, Barrow Neurological Institute. T. Becker: 1; C; National Institutes of Health. 4; C; Aneuvas Technologies, Inc. 5; C; Aneuvas Technologies, Inc, Barrow Neurological Institute, Northern Arizona University.